Measles‐associated pneumonia and hepatitis during the measles outbreak of 2018. Issue 2 (3rd October 2019) - Kakoullis, Loukas; Sampsonas, Fotios; Giannopoulou, Eleni; Kalogeropoulou, Christina; Papachristodoulou, Eleni; Tsiamita, Maria; Lykouras, Dimosthenis; Velissaris, Dimitrios; Karkoulias, Kyriakos; Spiropoulos, Kostas; Panos, George
Abstract: Background: Between 2017 and 2018, Greece experienced a measles outbreak, affecting >3000 patients, most of which were unvaccinated. Measles‐associated pneumonia (MAP) is the most common serious compilation of the disease, but very few recent reports regarding its presentation are available. Materials and Methods: Between January and May 2018, 11 adult patients presented to our department with acute measles virus infection, hypoxia and findings on chest X‐ray. Clinical, laboratory and radiological data were collected and assessed. Nine out of eleven patients had hypoxic respiratory failure. Other complications included hepatitis, cholestasis and myositis, which were observed in the majority of patients. All patients received supplementary oxygen administration, whereas five patients required continuous positive airway pressure ventilation. Scoring of the radiological examinations performed was most notable for the presence of reticular opacities and consolidations. Statistical analysis demonstrated a significant association between PaO2/FiO2 values and the presence of reticular opacities, with PaO2/FiO2 decreasing as the mean value of the reticular opacities score increased ( P  = .02). Conclusion: To our knowledge, this is the first report demonstrating an association between PaO2/FiO2 values and the presence of reticular opacities in patients with MAP. MAP should be suspected in any patient presenting with acute onset hypoxaemia and a reticular pattern on radiological examination, especially in outbreak settings. What is known: Measles infections are on the rise in Europe, with epidemics affecting several European countries, resulting from suboptimal immunisation. The most common serious complication of measles is pneumonia, which is more common in adult patients and can cause significant morbidity. It is the most common cause of death due to measles. What is new: In this report, we present 11 adults with measles‐associated pneumonia, who presented with the combination of acute measles virus infection, hypoxia and findings on chest X‐ray. To our knowledge, this is the first report demonstrating an association between the severity of hypoxaemia and the presence of reticular opacities on chest imaging studies.